Implementation of Practical Life Through Role-Play Method to Increase the Independence of 3-4 Year Old Children - Fadillah Ayu Andini; Sarah Emmanuel Haryono; Ayu Asmah (CV. Creative Tugu Pena, 2024)
Independence is a crucial aspect in early childhood development, which needs to be instilled early so that children grow into confident and resilient individuals, and are responsible. Initial observations at the Jabal Tsur Tajinan Playgroup (KB) showed that most children aged 3-4 years, 70%, had not shown optimal independence, still depending on adults for daily activities. This condition was caused by a lack of appropriate stimulation and the tendency of adults to be too helpful, which hindered the development of an independent attitude. This study aims to increase the independence of children aged 3-4 years at the Jabal Tsur Tajinan Playgroup. This study used a Classroom Action Research (CAR) design The PTK process is carried out in a repetitive cycle which includes Planning, Implementation (acting), Observation (observing), and reflection (reflecting). The study population was 12 children in group A aged 3-4 years at KB Jabal Tsur Tajinan, consisting of 6 girls and 6 boys. The research instrument was an observation sheet and an assessment rubric that included indicators of child independence. Dialysis data was descriptive. The results of initial observations showed that the average achievement of child independence was only 36%. After the implementation of Practical Life through role playing, there was a significant increase. In cycle I, the average achievement increased to 60%. Further increases occurred in cycle II, reaching an average of 92%. This approach has proven to be a significant learning tool to support the independence of early childhood, with children showing increased ability to carry out daily activities independently. These results are expected to be a reference for educators and PAUD institutions in developing fun learning models to optimally support children's independence.